COMBINING DISCRETE EVENT AND AGENT-BASED SIMULATION FOR REDUCING DRAFTEE’S WAITING TIME IN PHYSICAL EXAMINATION CENTERS - Ying, Kuo-Ching; Kittipittayakorn, Cholada (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
Modeling and simulation are widely used in many business domains, such as logistics, manufacturing, warehouses and hospitals. This research uses discrete event simulation (DES) combined with agent-based simulation (ABS) to improve draftees’ physical examination service by reducing the waiting time of the processes. We modeled a computer simulation to simulate a physical examination center in order to compare waiting time before and after applying the proposed approach. Data were derived from the physical examination centers admissions database and field observation. The model was validated by comparing the simulation results with waiting time, throughput time and doctors’ utilization obtained in real operation. The experimental results show that the combined DES and ABS model reduces waiting time by an average of 40.15% in patient waiting time. The overall results show that the proposed approach can reduce waiting time in an examination center, and can be applied to any physical examination process.